Implementasi Pendekatan Keterampilan Proses Sains Melalui Kegiatan Praktikum Berbantuan LKS Diagram Vee Terhadap Penguasaan Konsep Dan Sikap Ilmiah Siswa Pada Konsep Pertumbuhan Tanaman - Novebrianti, Sri Ajeng; Arip, Asep Ginanjar; Sulistyono, Sulistyono (Edubiologica, 2021)
The population in this study is all students of class XII SMA IT Al FaqihTasikmalaya with samples obtained using Purposive Sampling techniques as many as 44 students consisting of 22 samples in the experimental class and 22 samples in the control class. The instruments used in this study are lks validation sheet, learning implementation observation sheet, student scientific attitude observation sheet, description test sheet to know theunderstanding of student concepts and student response questionnaire to learning. The results showed that the KPS approach can be applied well through practical activities because the eightprinciples of the KPS approach can be facilitated, which include the ability to observe, calculate, measure, make predictions, carry out researching, collecting and analyzing data, interpreting data, and delivering results.In addition, in this study researchers have successfully developed LKS Diagram Vee through the application of components of Vee Diagram into the form of LKS that has been validated by experts including the components of focus questions, objects / events, concepts of principles & theories, transformations, and knowledgeacquisition. ofstudent concepts, namely the value of 2-tailed significance (t-tailed) 0.000 < 0.05 by applying the KPS approach through practical activities assisted by LKS Diagram Vee on the concept of Plant Growth. As well as the use of LKS Diagram Vee in practical learning can improve the scientific attitude of students in the experimental class to 93.8% who are on the criteria very well. Also supported by the results of the questionnaire student response to learning that is at a percentage of 94.5% that is on the criteria is very strong.